Evaluation of Cowpea Cultivars for Resistance to Cowpea Mottle Virus in Mokwa, Nigeria - A. S. Paiko; L.Y. Bello; A. C. Wada (Current Research Progress in Agricultural Sciences Vol. 9, 2025)
An evaluation of cowpea cultivars for resistance to cowpea mottle virus (CPMoV), a virus in the Carmovirus genus, was conducted at the Screen House of Niger State College of Agriculture. Five cowpea cultivars—Langbazo, Ezomilkigi, Ezobokun, Ezokapangi, and IT07K-277-2—were assessed for resistance to CPMoV. The experiment was arranged in a Completely Randomized Design (CRD) with five treatments plus an un-inoculated control, replicated three times. Data on disease incidence, plant height, and leaf number were collected at 3, 6, and 9 weeks post-inoculation (WPI) from randomly selected, tagged plants. Statistical analysis was performed using SPSS 16 to evaluate variance (ANOVA). Results indicated that control plants treated with buffer exhibited significantly better growth metrics than the virus-inoculated plants. Among the virus-inoculated cultivars, Langbazo and IT07K-277-2 showed significantly higher plant height and leaf number, suggesting they possess resistance traits. These resistant traits could potentially be incorporated into high-yielding genotypes to create CPMoV-resistant cowpea varieties. Additional studies are recommended to further investigate these cultivars’ defensive properties for potential use in hybridization programs.